The relationships of kinesiophobia and physical function and physical activity level in juvenile idiopathic arthritis - Leandra U. Woolnough; Logan Lentini; Sharareh Sharififar; Cong Chen; Heather K. Vincent (BMC, 2022)
Abstract Background Kinesiophobia may hinder physical performance measures and functional quality of life in children with juvenile idiopathic arthritis (JIA). This study aims to quantify differences in physical function in patients with JIA compared to healthy controls, and determine the effects of kinesiophobia on physical function and physical activity. Methods This was a comparative study of participants with JIA and healthy controls (JIA n = 26, control n = 17). All children with JIA had lower extremity joint involvement. Performance-based measures included gait speed, chair and stair navigation performance. Self-reported measures included Patient Reported Outcome Measurement Information System (PROMIS®) Physical Function Mobility, and Pain Interference and the Pediatric Functional Activity Brief Scale (Pedi-FABS). The Tampa Scale of Kinesiophobia (TSK-11) assessed patient fear of movement due to pain. Linear regression models were used to determine the contribution of TSK-11 scores on performance test and Pedi-FABS scores. Results Gait speeds were 11-15% slower, chair rise repetitions were 28% fewer, and stair ascent and descent times were 26-31% slower in JIA than controls (p < .05). PROMIS® Physical Function Mobility scores were 10% lower and Pain Interference scores were 2.6 times higher in JIA than healthy controls (p = .003). TSK-11 scores were higher in JIA than controls (p < .0001). After controlling for covariates, TSK-11 scores explained 11.7-26.5% of the variance of regression models for stair climb time, chair rise performance and Pedi-FABS scores (p < .05). Conclusions Children with JIA experience difficulty with tasks related to body transfers. Kinesiophobia is a significant contributor to the functional task performance and may impact clinical outcomes.